Deoxynivalenol induces oxidative stress, inflammatory response and apoptosis in bovine mammary epithelial cells. Issue 6 (18th August 2019) - Wang, Junmei; Jin, Yongcheng; Wu, Shunlu; Yu, Hao; Zhao, Yun; Fang, Hengtong; Shen, Jinglin; Zhou, Changhai; Fu, Yurong; Li, Ruihua; Wang, Rui; Wang, Junxiong; et al.
Abstract: Deoxynivalenol (DON) is a toxic secondary metabolite produced by Fusarium graminearum . It is one of the most common feed contaminants that poses a serious threat to the health and performance of dairy cows. This study investigated the in vitro cytotoxicity of DON on bovine mammary epithelial cells (MAC‐T). DON at different concentrations (0.25, 0.3, 0.5, 0.8, 1 or 2 μg/ml) inhibited the growth of MAC‐T cells after 24 hr of exposure ( p < .001). DON at 0.25 μg/ml increased lactate dehydrogenase (LDH) leakage ( p < .05); decreased glutathione (GSH) levels ( p < .001), total superoxide dismutase (T‐SOD) activity and total antioxidant capacity (T‐AOC; p < .01); and increased malondialdehyde (MDA) concentration ( p < .01) in MAC‐T cells after 24 hr of exposure. We also observed that DON increased reactive oxygen species (ROS) levels in cells incubated for 9, 15 and 24 hr ( p < .001). DON at 0.25 μg/ml triggered oxidative damage in MAC‐T cells. Furthermore, it induced an inflammatory response in the cells incubated for 9, 15 and 24 hr ( p < .05) by increasing the mRNA expression levels of nuclear factor kappa B, myeloid differentiation factor 88 (MyD88), tumour necrosis factor‐α (TNF‐α), interleukin‐1β (IL‐1β), IL‐6, cyclooxygenase‐2 and IL‐8. We further examined the effect of DON on apoptosis. DON prevented normal proliferation of MAC‐T cells by blocked cell cycle progression in 24 hr ( p < .001). In addition, the apoptosis rate measured using annexin V‐FITC significantly increased ( p < .05) with increase in the mRNA expression level of Bax ( p < .01) and increase in the Bax/Bcl‐2 ratio ( p < .01) in cells incubated for 24 hr. In summary, DON exerts toxic effects in MAC‐T cells by causing oxidative stress, inducing an inflammatory response, affecting cell cycle and leading to apoptosis.